LATE ONSET MANIA AS AN ORGANIC ILLNESS – A REVIEW OF CASE REPORTS. Issue 12 (15th November 2016) - Khan, Hina; Sami, Musa; Nilforooshan, Ramin
Abstract : Aims: First episode manic illness presenting over the age of 50, is an uncommon presentation, traditionally believed to have an organic basis. However to date there has been little systematic compilation of case reports. Methods: We undertook a literature search on MEDLINE, PsychInfo and EMBASE to identify case reports of first of mania or hypomania presenting over the age of 50. Results: 35 cases were identified. 29/35 (82%) had a suspected underlying organic cause. Organic causes included: vascular disease (including CADASIL), iatrogenic drug use, dementia, thyroid disease and meningitis. Vascular risk factors were present in 17/35 cases (48%). Focal imaging abnormalities were identified in 17/30 (57%) cases including basal ganglia, frontal lobe and thalamic lesions. In 10/35 (28%) of cases organic treatment contributed to successful remission of the manic episode. Conclusions: This review of case reports appears to add evidence of late onset mania having an organic basis. Whether this is a separate organic syndrome remains to be established. Our provisional findings suggest that such patient have a thorough medical screening in identifying an underlying cause.